Coincidence cloning of Alu PCR products. - Aslanidis, C (1991)
Coincidence cloning allows the isolation of sequences held in common by two genomic DNA populations. Human DNA from two human-hamster hybrid cell lines was amplified by Alu-repeat primers (Alu PCR) and the products originating from the shared human chromosomal region were cloned. To achieve this, human sequences were amplified with very similar Alu primers from the two different human-hamster hybrid cell lines. The products were then digested with an appropriate restriction enzyme (either BamHI or Sal I), combined, denatured, and reannealed. The derived heteroduplex molecules (originating from the human regions common to both cell lines) had single BamHI and Sal I cohesive ends due to the primers used, so that they could be cloned in a double-digested plasmid vector. We used this method to enrich about 10-fold for Alu PCR products from the human chromosome 19q13.2 region, resulting in a region-specific clone collection. About 90% of the recombinants with BamHI-Sal I inserts are derived from the common region. This approach allows the boundaries for the regional probe isolation to be defined by combinations of hybrids rather than single hybrid cell lines, thus permitting greater flexibility in the selection of regions for probe isolation.